Animalistic dehumanisation as a social influence strategy - Quiamzade, Alain; Lalot, Fanny (Frontiers in Psychology, 2023)
The phenomenon of animalistic dehumanisation has been extensively studied in social psychology but mostly as an intergroup relations tool, serving to justify the mistreatment of an outgroup. Surprisingly, however, dehumanisation has not been approached as an influence strategy, serving to convince the ingroup to mistreat an outgroup. In the present article, we investigate such possible influence effects. We propose that a message depicting an outgroup in animalised terms would lead to lasting unfavourable outgroup attitudes because the animal essence conveyed through the message would immunise ingroup members against potential subsequent counterinfluence attempts. In one experimental study we compared the effect of three influence messages depicting a despised outgroup (Roma beggars) in negative animalised vs. negative humanised vs. positive humanised terms, followed by a counterpropaganda message advocating for Roma beggars’ rights. Results show that the animalisation message leads to a lasting animalised perception of the outgroup (eliciting disgust and repugnancy) that resists exposure to the counterpropaganda positive message. In contrast, the negative humanisation message provokes a brief negative perception of the group (pre-counterpropaganda) that disappears after exposure to the counterpropaganda. The animalisation message also leads to more negative attitudes and behavioural intentions towards Roma beggars expressed after the counterpropaganda message (discrimination in the work place, hiring intentions, and social proximity), while the negative humanisation message does not, showing no difference from the positive humanisation message. These results suggest that animalistic dehumanisation can indeed serve as an influence strategy immunising influence targets against subsequent counterpropaganda attempts. We discuss implications in the light of essentialisation, forms of dehumanisation and group status, and current non-discriminatory norms.